Some problems and perspectives of endogeneous development in Hungarian agriculture - Szakal F.; Kiss J.; Angyan J. (Strengthening endogenous development patterns in European agriculture, 1993)
The authors summarise recent history of Hungarian agriculture as an ongoing negation of endogenous development potential external models was imposed. The paper stresses some of the now emerging perspectives.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)